The Effect of Low and Moderate Exercise on Hyperuricemia: Protocol for a Randomized Controlled Study - Hou, Yuning; Ma, Renyan; Gao, Song; Kaudimba, Keneilwe Kenny; Yan, Hongmei; Liu, Tiemin; Wang, Ru (Frontiers in Endocrinology, 2021)
Background: Hyperuricemia (HUA) is a metabolic disease by purine metabolism disorders. It is a risk factor for many chronic diseases, including hypertension, diabetes, and insulin resistance. Studies have shown that exercise can effectively reduce serum uric acid (SUA), but the optimal exercise dose, intensity, and mode of exercise for improving HUA have not been verified in clinical studies. Therefore, this study aims to explore the effect of different exercise intensities in improving SUA of patients with HUA. Methods and Analysis: A randomized, single-blind, parallel controlled trial will be conducted in this study. 186 HUA patients who meet the inclusion criteria will be randomly divided into a 1:1:1 ratio: (1) control group, (2) low-intensity exercise group (brisk walking, 57-63% maximum heart rate, 150 min/week, 12 months), and (3) moderate-intensity exercise group (jogging, 64-76% maximum heart rate, 150 min/week, 12 months). The three groups will receive the same health education and maintain their original eating habits. The primary outcomes will be SUA concentration, SUA concentration change (mg/dL), SUA change rate (%), and the proportion of HUA patients (SUA≤7.0 mg/dL). Secondary outcomes will include blood lipids, blood sugar, liver enzymes, creatinine, blood urea nitrogen, blood pressure, grip strength, cardiopulmonary function, weight, waist circumference, hip circumference. Each group of patients will go through an assessment at baseline, 3rd, 6th, and 12th months. Discussion: This study will evaluate the effect of 12-month low-intensity exercise and moderate-intensity exercise on HUA patients. We hypothesize that both low-intensity and moderate-intensity exercise would improve HUA as compared with no-exercise control, and that moderate-intensity exercise would be more effective than low-intensity exercise in improving HUA. These results can provide a basis for the current physical activity guidelines for HUA's healthy lifestyle management. Ethics and Dissemination: This study has been approved by the ethical review committee of the Shanghai University of Sport (approval number: 102772020RT005). Informed consent will be obtained from all participants or their guardians. The authors intend to submit the study findings to peer-reviewed journals or academic conferences to be published. Clinical Trial Registration: Chinese Clinical Trial Registry (ChiCTR2100042643).